Cross-border Cultural Relations of Croatia and Serbia: Milk and Honey if Money is Involved - Jelinčić, Daniela Angelina; Knezović, Sandro (Journal of Regional Security, 2021)
With the rise of creative industries, culture in international relations achieves strong competitive economic advantages. At the same time, it is often a fertile tool in reconciliation between connected communities and long-term consolidation of their relations. Economic peace theory claims economic interdependence as being the key factor in achieving peace between communities. Starting from this premise, this paper analysed the success of specific EU funding within cross-border cooperation schemes between Croatia and Serbia in enhancing social relations between the two states and their cooperation, as indirect effects. Adapted Conflict Management and Mitigation Matrix (CMM) served as a basis to con rm the assumption that international relations are enhanced if direct economic bene ts for the communities are involved. e research confirmed this assumption and provided recommendations for future EU financial instruments.